Equity Crowdfunding. Literature Review and Future Research Directions - Wanicki, Piotr; Bareja, Katarzyna; Giedroyć, Magdalena; Kaczmarczyk, Angelika; Piotrowska, Katarzyna (Publishing House of Wroclaw University of Economics and Business, 2025)
[The monograph entitled Equity Crowdfunding. Literature Review and Future Research Directions provides a comprehensive and systematic overview of the academic research on equity crowdfunding. Its main objective is to synthesise existing knowledge, structure the key thematic areas explored in the literature, and identify promising avenues for future research in this rapidly developing field of entrepreneurial finance. The opening chapter presents the research methodology, detailing the systematic literature review process applied to identify, select, and analyse relevant academic sources. This methodological framework ensures transparency, replicability, and a solid foundation for subsequent analyses. The core of the publication is organised around four thematic areas. The first explores the success factors of equity crowdfunding campaigns, identifying the determinants that influence fundraising outcomes. The second examines investor behaviour, focusing on motivations, decision-making processes, and behavioural patterns. The third discusses the mechanisms of operation of equity crowdfunding platforms, including regulatory, technological, and market aspects. The fourth area analyses the objects of funding, looking at the types of ventures and industries most commonly financed through this model. The monograph concludes with a discussion and future research directions, pointing to existing gaps in knowledge and proposing areas for further academic exploration. By combining a rigorous methodological approach with structured thematic analysis, this publication contributes to the international debate on alternative finance, innovation, and entrepreneurial ecosystems.] z zapowiedzi
s. 75
Quote as: Wanicki, P., Bareja, K., Giedroyć, M., Kaczmarczyk, A., & Piotrowska, K. (2025). Equity Crowdfunding. Literature Review and Future Research Directions. Publishing House of Wroclaw University of Economics and Business.
Keywords: equity crowdfunding; systematic literature review; entrepreneurial finance; alternative finance; investor behaviour; crowdfunding mechanism